Impact of Nurse-led Mindfulness and Stress Reduction Programs on Patients with Anxiety and Depression: A Systematic Review - Arti, Arti; Raheja, Simpi; Sonia, Sonia (Journal of Neonatal Surgery, 2025)
Background: Anxiety and depression are prevalent mental health conditions globally. Nurse-led mindfulness and stress reduction interventions have emerged as accessible, cost-effective strategies to support patients' mental well-being. However, the effectiveness of these interventions requires synthesis through systematic evidence. Objective: To evaluate the effectiveness of nurse-led mindfulness and stress reduction programs on anxiety and depression outcomes in adult patients. Methods: A systematic review was conducted following PRISMA guidelines. Six peer-reviewed studies published between 2015 and 2024, sourced from PubMed, CINAHL, PsycINFO, and Scopus, were included. Eligibility criteria included randomized controlled trials (RCTs) and quasi-experimental studies that assessed nurse-led mindfulness or stress reduction programs targeting anxiety and/or depression in adult populations. Data were extracted and pooled using a random-effects meta-analysis model. Results: The review included 582 participants across six studies (n = 288 intervention, n = 294 control). The pooled effect size for anxiety was significant, with a standardized mean difference (SMD) of −0.64 (95% CI: −0.89 to −0.39; p < 0.001), indicating a moderate effect of the intervention. For depression, the pooled SMD was −0.57 (95% CI: −0.81 to −0.33; p < 0.001), also reflecting a moderate reduction in symptoms. Heterogeneity was moderate (I² = 48% for anxiety; I² = 52% for depression). No major adverse events were reported. Intervention durations ranged from 4 to 12 weeks, and commonly used techniques included guided meditation, breathing exercises, and mindful awareness practices. Conclusion: Nurse-led mindfulness and stress reduction interventions show moderate and statistically significant effectiveness in reducing anxiety and depression symptoms in adult patients. These findings support the integration of nurse-delivered mental health strategies into routine care, particularly in settings with limited access to specialized mental health professionals.